The internet con : how to seize the means of computation - Doctorow, Cory (Verso, 2023)
"This is a call to arms about how to bring the big online platforms to their knees. It concerns the question of interoperability: the way that Facebook, Twitter etc make it very difficult for you to move and own your data. Doctorow shows that this is not a problem of technology but of law, business and apathy in face of growing monopolies. He covers ground such as anti-trust, and how the platforms deal with take down orders. Through this he shows how the FANGS became too powerful - and show us what we can do about it!"--